The Association Between Early and Late Onset Severe Preeclampsia and the Incidence of Low Birth Weight at Muhammadiyah Hospital Palembang - Aziz, Aryani; Umniyah, Putri (Journal of Comprehensive Science, 2025)
Severe preeclampsia (PE) is a major cause of maternal and perinatal complications. Early-onset (EOPE) and late-onset (LOPE) severe preeclampsia can impact fetal growth, leading to low birth weight (LBW). This study aims to determine the association between EOPE, LOPE, and LBW incidence at Muhammadiyah Hospital Palembang. A retrospective case-control study was conducted from October 2021 to January 2022. A total of 269 cases (10 EOPE, 259 LOPE) and 269 controls were analyzed. Data were obtained from hospital records and assessed using the chi-square test and odds ratio (OR). Results show LOPE prevalence (96.3%) was higher than EOPE (3.7%). LBW incidence was 100% in EOPE cases and 21.18% in LOPE cases. A significant association was found between EOPE, LOPE, and LBW (p = 0.001, OR = 63.75), indicating a 63.75-fold increased risk. Both EOPE and LOPE increase the risk of LBW, with EOPE posing a greater risk. Early detection and management of preeclampsia are crucial for improving perinatal outcomes.